Smartphone app-based approximation of time spent with atrial fibrillation and symptoms in patients after catheter ablation: data from the TeleCheck-AF project - Sandgren, Emma; Hermans, Astrid N L; Gawalko, Monika; Betz, Konstanze; Sohaib, Afzal; Fung, Chi Ho; Hillmann, Henrike A K; van der Velden, Rachel M J; Verhaert, Dominique; Scherr, Daniel; Sultan, Arian; Steven, Daniel; et al. (Europace (London, England), 2024)
Abstract Aims Reduction of atrial fibrillation (AF) burden is the preferred outcome measure over categorical AF rhythm recurrence after AF ablation. In this sub-analysis of the TeleCheck-AF project, we tested the feasibility of smartphone app-based approximation of time spent with AF and/or symptoms. Methods and results Patients scheduled for at least one teleconsultation during the 12-month follow-up after AF ablation were instructed to use a smartphone photoplethysmography-based application for simultaneous symptom and rhythm monitoring three times daily for 1 week. Proxies of time spent with AF and/or symptoms (% recordings, load, and % days), temporal aggregation of AF and/or symptoms (density), and symptom–rhythm correlation (SRC) were assessed. In total, 484 patients (60% male, 62 ± 9.9 years) were included. Adherence, motivation, and patient satisfaction were high. %AF recordings, AF load, and %AF days (rs = 0.88–0.95) and %symptom recordings, symptom load, and %symptom days (rs = 0.95–0.98) showed positive correlations. The SRC correlated negatively with time spent with symptoms (rs = −0.65–0.90) and with time spent with AF (rs = −0.31–0.34). In patients with paroxysmal AF before ablation and AF during the monitoring period, 87% (n = 39/44) had a low-density score <50% (‘paroxysmal AF pattern’) while 5% (n = 2/44) had a high-density score >90% (‘persistent AF pattern’). Corresponding numbers for patients with persistent AF before ablation were 48% (n = 11/23) and 43% (n = 10/23), respectively. Conclusion On-demand, app-based simultaneous rhythm and symptom assessment provides objective proxies of time spent with AF and/or symptoms and SRC, which may assist in assessing AF and symptom outcomes after AF ablation. Graphical Abstract Graphical Abstract